GAMES-BASED LEARNING INTEGRATED ENTRY POINT STRATEGY ASSISTED BY AUGMENTED REALITY FOR MATHEMATICAL PROBLEM SOLVING - Nuhyal Ulia; Rida Fironika Kusumadewi; Mohamad Hariyono; Rizky Tantina; Afifatul Maulida (Universitas Labuhanbatu, 2026)
Purpose –To examine the effectiveness and the effect of Games-Based Learning Integrated Entry Point Strategy Assisted by Augmented Reality on elementary school students' mathematical problem-solving abilities.Methodology – The type of research used is a Quasi-experimental design with a pretest-posttest-only control group design. Data collection uses test instruments, with data analysis techniques including normality tests, homogeneity tests, paired-sample t-tests, gain t-tests, and independent t-tests. The population in this study was fifth-grade students of SDN 1 Purwogondo and SDN 01 Ngagel. The sample in this study consisted of 30 students, 15 in the experimental group and 15 in the control group.Findings – Game-based learning integrated with an entry point strategy assisted by Augmented Reality is effective on elementary school students' mathematical problem-solving abilities, as indicated by the results of the independent t-test obtained sig 0.000 < 0.05 and the results of the paired sample t-test obtained sig 0.000 < 0.05 with a high gain value of 0.75. meaning there is an increase in students' mathematical problem-solving abilities after Game-based learning integrated with an entry point strategy assisted by Augmented RealityContribution – This study contributes to elementary school teacher education by integrating an Augmented Reality-assisted entry point strategy into a Games-Based Learning model that effectively improves elementary school students' mathematical problem-solving skills